Indoles from Alkynes and Aryl Azides: Scope and Theoretical Assessment of Ruthenium Porphyrin‐Catalyzed Reactions. Issue 72 (2nd December 2019) - Intrieri, Daniela; Carminati, Daniela Maria; Zardi, Paolo; Damiano, Caterina; Manca, Gabriele; Gallo, Emma; Mealli, Carlo
Abstract: A symbiotic experimental/computational study analyzed the Ru(TPP)(NAr)2 ‐catalyzed one‐pot formation of indoles from alkynes and aryl azides. Thirty different C3 ‐substituted indoles were synthesized and the best performance, in term of yields and regioselectivities, was observed when reacting ArC≡CH alkynes with 3, 5‐(EWG)2 C6 H3 N3 azides, whereas the reaction was less efficient when using electron‐rich aryl azides. A DFT analysis describes the reaction mechanism in terms of the energy costs and orbital/electronic evolutions; the limited reactivity of electron‐rich azides was also justified. In summary, PhC≡CH alkyne interacts with one NAr imido ligand of Ru(TPP)(NAr)2 to give a residually dangling C(Ph) group, which, by coupling with a C(H) unit of the N ‐aryl substituent, forms a 5+6 bicyclic molecule. In the process, two subsequent spin changes allow inverting the conformation of the sp 2 C(Ph) atom and its consequent electrophilic‐like attack to the aromatic ring. The bicycle isomerizes to indole via a two‐step outer sphere H‐migration. Eventually, a ′Ru(TPP)(NAr)′ mono ‐imido active catalyst is reformed after each azide/alkyne reaction. Abstract : The Ru(TPP)(NAr)2 ‐catalyzed one‐pot formation of indoles from alkynes and aryl azides was analyzed by a synergic experimental/computational study. The reaction was effective for the synthesis of differently C3 ‐substituted indoles and the DFT investigation elucidated the energy costs as well as the associated orbital and electronic evolutions of the reaction.